Glissant and the middle passage : philosophy, beginning, abyss - Drabinski, John E., 1968- (Thinking theory., 2019)
A reevaluation of Édouard Glissant that centers on the catastrophe of the Middle Passage and creates deep, original theories of trauma and Caribbeanness. While philosophy has undertaken the work of accounting for Europe's traumatic history, the field has not shown the same attention to the catastrophe known as the Middle Passage. It is a history that requires its own ideas that emerge organically from the societies that experienced the Middle Passage and its consequences firsthand. Glissant and the Middle Passage offers a new, important approach to this neglected calamity by examining the thought of Édouard Glissant, particularly his development of Caribbeanness as a critical concept rooted in the experience of the slave trade and its aftermath in colonialism. In dialogue with key theorists of catastrophe and trauma--including Aime Cesaire, Frantz Fanon, George Lamming, Gilles Deleuze, Felix Guattari, Derek Walcott, as well as key figures in Holocaust studies--Glissant and the Middle Passage hones a sharp sense of the specifically Caribbean varieties of loss, developing them into a transformative philosophical idea. Using the Plantation as a critical concept, John E. Drabinski creolizes notions of rhizome and nomad, examining what kinds of aesthetics grow from these roots and offering reconsiderations of what constitutes intellectual work and cultural production. Glissant and the Middle Passage establishes Glissant's proper place as a key theorist of ruin, catastrophe, abyss, and memory. Identifying his insistence on memories and histories tied to place as the crucial geography at the heart of his work, this book imparts an innovative new response to the specific historical experiences of the Middle Passage.